Comparison Between Thermo Luminescence Dosimeter and Planning System Dose Calculation in The Brain and Spinal Cord Tumour - Hegazy, Ehab A (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Radiotherapy of Spinal cord and brain tumor requires High care due to considerable changes in the white matter of the brain, which consequently lead to a reduction of patient learning and mental skills. It is considered a very critical tumor due to high sensitivity of gross volume location and normal tissues surrounding it, including eye, heart, plate thyroid, and testis. XiO planning systems, TLD dosimeter found in Mansoura university oncology department, CMS XIO USA TPS were compared using electron and photon beams with different energies at a different site in target volume and organs at risk. We conclude that regular calibration of planning systems and direct measurement of the dose delivered to main target and organs at risk should be done to avoid the difference between XiO planning systems and direct measurement by TLd.